Субъективная картина истории народа - Ахмеров, Р. (Социология: теория, методы, маркетинг, 2007)
The author empirically substantiates an ethno-psychological phenomenon named "subjective image of the history of nationality" as ideas about historic past, present, and future of the nationality represented in an individual's consciousness. Moreover, methods for studying this phenomenon are developed and suggested. It is established that the subjective image of the history of nationality is not directly related to knowledge of history as that was officially explained and accepted. This subjective image looks stable over time and has similar characteristics among the representatives of one nationality or ethnic group even if they live in different localities.The author proves the possibility to comparatively analyze the subjective history of different nationalities (or ethnic groups). Some questions of the further research on interrelation between subjectively estimated and officially accepted history of nationality are discussed as well.